Stakeholder Mapping in Kenya reveals key community changemakers in management of rangelands - Akivaga, Allan; Mukalo, Irene (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Being scaled through AICCRA activities in Kenya, participatory rangeland management (PRM) is a community-led process developed by the International Livestock Research Institute (ILRI) and partners to strengthen local management institutions, promote greater involvement of women and support communities to develop and implement a rangeland management plan.